Về một bài toán thiết kế phương án minimax kiểm tra nghiệm thu thống kê - Tùng, Nguyễn Thanh (Journal of Computer Science and Cybernetics, 2016)
The purpose of this paper is to  investigate the problem of designing minimax-regret attributes sampling plans under the following assumptions: -         The production process in control with process average varies at random from lot to  lot  and  othing is known about this variation. -         Two decisions which will be considered regarding the remaider of lot are acceptance and rejection. -         The per item costs for inspection, acceptance and rejection are all linear functions of the fraction defective in lot. We study some properties of the optimal sampling plans. These properties are used to devise an  improved and efficient algorithm for determination of such plans. Numerical examples are presented to illustrate the potential computational savings of the algorithm.